Efficacy and safety of laser‐assisted combination chemotherapy: A follow‐up study of treatment with 5‐fluorouracil and cisplatin for basal cell carcinoma. Issue 1 (5th December 2021) - Fredman, Gabriella; Wenande, Emily; Hendel, Kristoffer; Togsverd‐Bo, Katrine; Haedersdal, Merete
Abstract: Background and Objectives: There is a growing need for effective topical treatments for basal cell carcinoma (BCC). By altering the skin barrier, ablative fractional lasers (AFLs) enhance cutaneous uptake of the synergistic chemotherapeutic agents, cisplatin, and 5‐fluorouracil (5‐FU). In our recently reported clinical trial, AFL‐assisted delivery of cisplatin and 5‐FU showed favorable short‐term clearance rates of 95% with good cosmetic results at 3 months. This follow‐up study assessed sustained tumor clearance, safety, and cosmesis in the same patient cohort, observed 6‐ and 12‐months posttreatment. Materials and Methods: This follow‐up study assessed AFL‐assisted cisplatin and 5‐FU in low‐risk BCC. Among the 18/19 patients who achieved clinical tumor clearance in our 3‐months primary trial, all were included for a 6‐months follow‐up. At 12 months, 17/19 were included due to one 6‐month residual. During follow‐up visits, treated areas were evaluated for signs of recurrent tumour by clinical inspection and optical coherence tomography (OCT). Residual tumors were confirmed histologically. Cosmetic outcome was evaluated at both follow‐up visits by patients and physicians. Results: Overall, complete tumor clearance was 89% (17/19) and 79% (15/19) at 6 and 12 months, respectively. Clearance rate for superficial BCCs (sBCCs) 1 year after treatment was 100% (6/6) and lower for nodular BCC (nBCC) at 69% (9/13). Among recurrent tumors, 67% (2/3) had received only a single treatment and all were of the nodular subtype, situated in the head and neck area. All histologically confirmed BCC recurrences were identified by OCT. Cosmetic outcomes were similarly rated "good" or "excellent" by patients and evaluators ( p = 0.289 and p = 0.250). Treatment‐related local skin reactions were mild and tolerable, consisting of persisting erythema in two patients at the end of the study. Dyspigmentation was commonly observed at both follow‐up visits, while the appearance of scarring resolved in the majority of patients between 6 months (56%; 10/18) and 12 months (76%; 13/17). Conclusion: AFL‐assisted cisplatin + 5‐FU in double sessions represents an acceptable and safe treatment strategy for low‐risk sBCC, while clearance rates following single treatment or for nBCC seem inferior. This intensified topical strategy may be best suited to cases of multiple lesions or in instances where surgical excision or extended courses of at‐home therapy is challenging.